2021
DOI: 10.1136/bmj.n1098
|View full text |Cite
|
Sign up to set email alerts
|

Risk of clinical sequelae after the acute phase of SARS-CoV-2 infection: retrospective cohort study

Abstract: Objective To evaluate the excess risk and relative hazards for developing incident clinical sequelae after the acute phase of SARS-CoV-2 infection in adults aged 18-65. Design Retrospective cohort study. Setting Three merged data sources from a large United States health plan: a large national administrative claims database, an outpatient laboratory testing database, and an inpatient hospital admissions data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

25
347
4
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(430 citation statements)
references
References 44 publications
25
347
4
6
Order By: Relevance
“…There have been recent hypotheses regarding the cause of cognitive impairment associated with long COVID [ 2 , 3 ]. However, the prevalence of the systemic effects of long COVID are now emerging from the analysis of global patient electronic records and registries, including in the USA and the UK [ 4 , 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been recent hypotheses regarding the cause of cognitive impairment associated with long COVID [ 2 , 3 ]. However, the prevalence of the systemic effects of long COVID are now emerging from the analysis of global patient electronic records and registries, including in the USA and the UK [ 4 , 5 ].…”
mentioning
confidence: 99%
“…In May 2021, Daugherty and colleagues published the findings from a retrospective analysis of three US patient databases to evaluate the prevalence of persistent symptoms after the acute phase of SARS-CoV-2 infection in 193,113 adults between 18–65 years of age [ 5 ]. The study included an outpatient laboratory testing database, an extensive US national administrative claims database, and a database of hospital admissions, with clinical sequelae identified by ICD-10 codes and defined as being present from 21 days after the date of first SARS-CoV-2 diagnosis [ 5 ]. This study identified more than 50 clinical sequelae, or types of long COVID, in patients who had recovered from the acute phase of SARS-CoV-2 infection [ 5 ].…”
mentioning
confidence: 99%
“…The recent upsurge in India has brought to our attention -mucormycosis, a rare complication developing in patients with COVID-19, diabetes and inappropriate use of dexamethasone (12). We have now evidence available on COVID sequelae we have been concerned about, pulmonary and cardiovascular consequences -4-6 months follow-up studies after COVID-19 that looked at hospitalizations and death rate (13,14). In a study of 73 435 nonhospitalized and 13 645 hospitalized patients with COVID-19 authors demonstrated a 1.46 times higher risk of death and increased hospitalizations during 6 months with respiratory, CV and other conditions in COVID-19 patients as compared to patients without COVID-19.…”
mentioning
confidence: 99%
“…Excess in CV burden and hospitalizations after mild, moderate severe forms of COVID-19 were due to hypertension, arrhythmias, chest pain, HF, and coronary atherosclerosis (13). Recent analysis of 4 months follow-up after acute phase of about 250 000 patients with COVID-19 demonstrated increased risk of hospitalizations with respiratory failure, arrhythmias, diabetes, myocarditis, hypercoagulability after acute disease, risk was higher in older age patients with comorbidities, though younger adults were also at risk (14). These studies testify that COVID-19 is associated with poorer prognosis than seasonal influenza, CV hospitalizations may be due to new onset but also due to worsening of pre-existing conditions.…”
mentioning
confidence: 99%
“…Limping from one crisis to the next is negligence, and quitting a failed approach is often better than gritting it out 10. More evidence continues to emerge on the growing burden of long term sequelae of SARS-CoV-2 infection, and how they overlap and differ from the sequelae of other viral illnesses 1112. This adds to the existing pressures on health services of managing patients at a distance, providing mental health services for pandemic and climate emergencies, and finding solutions to workforce pressures and doctors’ training needs 131415…”
mentioning
confidence: 99%